Simultaneous biochemical and functional phenotyping of single circulating tumor cells using ultrahigh throughput and recovery microfluidic devices. Issue 18 (4th August 2021) - Liu, Yang; Zhao, Wujun; Cheng, Rui; Hodgson, Jamie; Egan, Mary; Pope, Christen N. Cooper; Nikolinakos, Petros G.; Mao, Leidong
Abstract : Integrated inertial ferrohydrodynamic cell separation (i 2 FCS) enables the isolation of circulating tumor cells with a high recovery rate and high throughput. The functional properties of the isolated CTCs could be evaluated with the migration assay. Abstract : Profiling circulating tumour cells (CTCs) in cancer patients' blood samples is critical to understand the complex and dynamic nature of metastasis. This task is challenged by the fact that CTCs are not only extremely rare in circulation but also highly heterogeneous in their molecular programs and cellular functions. Here we report a combinational approach for the simultaneous biochemical and functional phenotyping of patient-derived CTCs, using an integrated inertial ferrohydrodynamic cell separation (i 2 FCS) method and a single-cell microfluidic migration assay. This combinatorial approach offers unique capability to profile CTCs on the basis of their surface expression and migratory characteristics. We achieve this using the i 2 FCS method that successfully processes whole blood samples in a tumor cell marker and size agnostic manner. The i 2 FCS method enables an ultrahigh blood sample processing throughput of up to 2 × 10 5 cells s −1 with a blood sample flow rate of 60 mL h −1 . Its short processing time (10 minutes for a 10 mL sample), together with a close-to-complete CTC recovery (99.70% recovery rate) and a low WBC contamination (4.07-log depletion rate by removing 99.992% of leukocytes), results in adequate and functional CTCs for subsequent studies in the single-cell migration device. For the first time, we employ this new approach to query CTCs with single-cell resolution in accordance with their expression of phenotypic surface markers and migration properties, revealing the dynamic phenotypes and the existence of a high-motility subpopulation of CTCs in blood samples from metastatic lung cancer patients. This method could be adopted to study the biological and clinical value of invasive CTC phenotypes.